Ambiguity as a Communicative Style: A Study of Rufftown Records - Nkansah, Samuel Kwesi; Gyasi, Rexford Boateng (Advances in Social Sciences Research Journal, 2021)
Songs are one of the oldest forms of literature and they continue to play important roles in the socialization of members of a society. Considering the importance of songs, this study sought to analyze ambiguity in Ghanaian songs focusing on songs produced by one of the vibrant production houses in Ghana ‘Ruff town Records’. The study was based on 15 sampled songs by Ebony Reigns and Wendy Shay, the leading artistes of the record label. The study revealed instances of ambiguity in 10 of the sampled songs with the causes of these indeterminacies being mainly phonological intonation and lexical choices. These ambiguities were euphemistically deployed mostly to highlight sexual images. The study has implications for revealing the trends and patterns of contemporary Ghanaian music. It is therefore recommended that more studies should be carried out on Ghanaian songs, focusing on other styles and presentation techniques employed by song writers.